An experimental and theoretical comparative study of the entrapment and release of dexamethasone from micellar and vesicular aggregates of PAMAM-PCL dendrimers. (August 2017) - Avila-Salas, Fabián; Pereira, Alfredo; Rojas, Moisés A.; Saavedra-Torres, Mario; Montecinos, Rodrigo; Bonardd, Sebastián; Quezada, Caterina; Saldías, Soledad; Díaz Díaz, David; Leiva, Angel; Radic, Deodato; Saldías, César
Graphical abstract: Snapshots of thei nitial state of the PAMAM-PCL dendrimer model with four dexamethasone molecules (a, b). Snapshots of the trajectories of the adopted conformations by the dendrimer and the interactions with dexamethasone after 10 ns of simulation into: (c) CHF, (d) THF, (e) CHF/WAT and (f) THF/WAT solvent boxes. Snapshots of the trajectories of the conformation of dendrimer with trapped dexamethasone into a water box after 24 ns of simulation are shown in (g) and (h). Highlights: Vesicular and micellar aggregates by simple emulsion (O/W) of PAMAM-PCL dendrimers were prepared. The solubilization of dexamethasone into dendrimer aggregates is an enthalpy-driven process. The drug release resulted to be a combination of both diffusion and eroding of dendrimeric matrix mechanisms. Molecular dynamic simulation provided a possible explanation of the formation of different types of aggregates. Abstract: Self-assembling dendrimers in aqueous solution have attracted many efforts focused on the rationalization and development of consistent strategies to design carriers that are useful in the field of drug release. In this way, amphiphilic dendrimers with specific structural features and self-assembling behaviors in aqueous media would enable drug entrapment as well as drug release over a determined time period. In this work, we report the synthesis and characterization of poly(amido-amine)-b-poly(ε-caprolactone) (PAMAM-PCL) amphiphilic dendrimers and their use in the preparation of micellar and vesicular aggregates. The ability to form suitable carriers of amphiphilic dendrimers using dexamethasone as a model drug was assessed. Using the ultrasonic-assisted precipitation method, PAMAM-PCL 1 and PAMAM-PCL 2 self-assembled into micelles and vesicles were obtained. The critical aggregation concentration (C.A.C.), hydrophilic-hydrophobic balance and aggregate sizes were found to mainly depend on the type of dendrimer used. Characterization of PAMAM-PCL aggregates by transmission electron microscopy (TEM), dynamic light scattering (DLS), UV–visible, fluorescence and zeta potential (ξ) was carried out. The standard free energies of solubilization, ΔGs °, of dexamethasone into PAMAM-PCL aggregates were obtained from the partition coefficient between the aqueous and the aggregate phases. ΔGs ° is notoriously dependent on the type of dendrimer and aggregate employed. In addition, by in vitro studies, a combination of diffusion and eroding dendrimeric matrix mechanisms for drug release could be established. Finally, all-atom molecular dynamic simulations helped us to gain insight into the conformational behavior and interactions between the PAMAM-PCL dendrimer and dexamethasone in different solvents and their respective mixtures with water.